Pentingnya Konseling dalam Menumbuhkan Sikap Moderat Beragama - Ahmad Andry Budianto; A. Khairuddin (Maddah : Jurnal Komunikasi dan Konseling Islam, 2024)
This study aims to examine in depth how counseling can contribute to fostering moderate religious attitudes in the community. The research method in this study is a qualitative method with a phenomenological research type, this research will explore the counselor's experience in helping counselees develop a balanced, tolerant, and inclusive understanding of religion. In addition, this study will also explore the challenges and obstacles faced by counselors in implementing counseling approaches related to religious issues. Factors such as cultural background, personal values, and counselor competence will be the focus of the study. In addition, to understand the role of counseling in fostering moderate religious attitudes, this study will use a qualitative approach. The results of this study indicate that counselors can apply various techniques to support counselees to be more open and tolerant of religious diversity. These techniques include building a sense of security and trust, exploring the religious background of the counselee, encouraging critical reflection, providing balanced information, exploring commonalities between traditions, facilitating dialogue between religious believers, and encouraging the counselee to have direct interfaith experiences. The application of these techniques proved to be effective in helping counselees to become more open, tolerant, and appreciative of religious perspectives that differ from their own. The findings provide practical implications for counselors in facilitating the development of religious moderation and enhancing social cohesion in religiously diverse communities.